A kind of coal gangue-based low-carbon cement with high resistance to chloride ion penetration and preparation method thereof
By using modified carbonate fillers, aluminum-rich mineral correction materials and fine aggregates in coal gangue-based low-carbohydrate cement to perform step-graining preparation, the problem of insufficient anti-chlorine ion permeability of cement is solved, and the anti-chlorine ion permeability, toughness and strength of cement is significantly improved.
Patent Information
- Application Number
- CN202510224407.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-27
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2045-02-27
AI Technical Summary
The existing coal gangue-based low-carb cement has insufficient chloride ion permeability and is difficult to meet the durability requirements in harsh environments.
The step-graining preparation is carried out by using styrene acrylate emulsion modified limestone powder, shell powder and magnesite tailings as carbonate fillers, combined with aluminum-rich mineral correction materials and fine aggregates, to improve the anti-chlorine ion permeability and mechanical properties of the cement.
It significantly improves the permeability, toughness and strength of the cement to resist chloride ion, and overcomes the problems of high porosity and poor permeability of coal gangue cement.
Smart Images

Figure CN119683962B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of civil engineering, and in particular relates to a gangue-based low-carbon cement with high resistance to chloride ion penetration and a preparation method thereof. Background Art
[0002] Traditional silicate cement production has high energy consumption, large carbon emissions, and poor resistance to chloride ion permeability, making it difficult to meet the durability requirements in harsh environments such as marine engineering. Therefore, the development of new cementitious materials with low carbon and high resistance to chloride ion permeability has become a research hotspot.
[0003] Coal gangue is solid waste generated during coal mining and washing. Its large-scale storage not only occupies land, but also pollutes the environment. However, coal gangue contains a certain amount of active SiO2 and Al2O3. After proper treatment, it can be used as an auxiliary cementitious material to partially replace cement clinker and reduce carbon emissions from cement production.
[0004] In recent years, researchers have tried to compound coal gangue with industrial waste residues such as slag and fly ash, and improve its activity through mechanical activation and chemical excitation to prepare coal gangue-based low-carbon cement with excellent performance. However, how to further improve the chloride ion permeability of coal gangue-based cement to meet the application requirements in harsh environments is still an urgent problem to be solved.
[0005] For example, CN119118541A discloses a method for preparing cement clinker using coal gangue as raw material, which comprises the following steps: crushing the coal gangue and transferring it into a ball mill, adding perovskite manganese oxide nano powder for ball milling and mixing, and obtaining modified coal gangue powder after the ball milling and mixing; mixing the limestone, manganese slag, copper slag, silica fume, disodium hydrogen phosphate, and modified coal gangue powder by acoustic resonance, calcining after mixing, and obtaining cement clinker after cooling. Although this application can improve the compressive strength of the clinker, the resistance to chloride ion permeability still needs to be improved.
[0006] For example, CN105669056A discloses a low-carbon cement clinker and its preparation method and application, wherein the raw materials for preparing the cement clinker are silicon-aluminum-containing materials, limestone and industrial tailings, wherein the silicon-aluminum-containing materials are a mixture of one or more of low-grade bauxite, fly ash, red mud and coal gangue; the raw materials are mixed and ground, and the particle size after grinding is required to be less than 15% on a 0.08 mm square hole sieve, and the ground raw materials are calcined at a calcination temperature of 1150 to 1350°C for 10 to 40 minutes, and the low-carbon cement clinker is obtained after cooling. Although this application provides the early and late strength of cement clinker, the toughness of cement clinker is reduced.
[0007] In view of this, the present invention is proposed. Summary of the invention
[0008] The purpose of the present invention is to provide a gangue-based low-carbon cement with high resistance to chloride ion permeability and a preparation method thereof. The cement provided by the present invention has excellent high resistance to chloride ion permeability, and in addition, the toughness and strength of the cement are also highly improved.
[0009] In order to achieve the above object, the present invention provides the following technical solutions:
[0010] In a first aspect, the present invention provides a gangue-based low-carbon cement with high resistance to chloride ion penetration, comprising the following components in parts by weight:
[0011] 30-50 parts of cement clinker;
[0012] 30-50 parts of coal gangue;
[0013] 5-15 parts of aluminum-rich mineral correction material;
[0014] 10-20 parts of carbonate filler;
[0015] 10-15 parts of fine aggregate;
[0016] Sulfate component 5-10 parts;
[0017] Performance improver 0.4-0.8 parts;
[0018] The carbonate filler is obtained by modifying limestone powder, shell powder and magnesite tailings with styrene acrylate emulsion.
[0019] The present invention modifies limestone powder, shell powder and magnesite tailings by styrene acrylic ester emulsion, so that the cement clinker has excellent toughness, strength and high chloride ion resistance.
[0020] Specifically, since the main components of limestone powder, shell powder, and magnesite tailings are calcium carbonate and magnesium carbonate, their compatibility with cement is poor, and styrene acrylate emulsion can improve the compatibility of magnesium carbonate, calcium carbonate and cement, improve the bonding strength of cement-based composite materials, and then enhance the mechanical properties of cement such as compression and bending resistance, so that it can better withstand external loads. In addition, magnesium carbonate and calcium carbonate can reduce the porosity of the cement matrix, thereby improving its impermeability and strength. And the addition of magnesium carbonate and calcium carbonate can also improve the early strength of concrete, but simply adding magnesium carbonate and calcium carbonate cannot improve the toughness of the cement matrix. The present invention utilizes styrene acrylate emulsion to modify calcium carbonate, introduces it into the cement mixture, and can fine-tune the pore structure of the cement matrix. The styrene-acrylate emulsion acts as a seed for magnesium carbonate and calcium carbonate. In fact, the styrene-acrylate emulsion adheres to the surface of magnesium carbonate and calcium carbonate, significantly reducing the interfacial energy, which is conducive to crystallization in the form of thin layer stacking, promoting the formation of magnesium carbonate and calcium carbonate crystals with higher crystallinity, and prompting a large number of magnesium carbonate and calcium carbonate crystals to recrystallize, which effectively occupy the voids in the matrix. In addition, by forming a flexible interface layer, the styrene-acrylate emulsion further assists in pore filling. This fine-tuning of the pore structure by the styrene-acrylate emulsion can significantly improve the mechanical properties and resistance to chloride ion permeability of cement.
[0021] In a preferred embodiment, the preparation method of the carbonate filler is as follows:
[0022] Limestone, shell powder and magnesite tailings are ground and sieved to obtain a solid phase, the solid phase is mixed with styrene, acrylate, anhydrous ethanol and water, an initiator is added, and after reaction, the carbonate filler is obtained by filtering and washing.
[0023] In a preferred embodiment, the mass ratio of the limestone, shell powder and magnesite tailings is 1:(2-5):(4-10).
[0024] In a preferred embodiment, the sieve used for screening is 200-500 mesh.
[0025] In a preferred embodiment, the mass ratio of the solid phase, styrene, acrylate, initiator, anhydrous ethanol and water is 1: (5-8): (10-17): (2-8): (42-63): (60-100).
[0026] In a preferred embodiment, the initiator is potassium persulfate.
[0027] In a preferred embodiment, the reaction is a reflux reaction, the reaction temperature is 50-80° C., and the reaction time is 3-8 h.
[0028] The present invention significantly improves the strength and chloride ion permeability of cement by compounding the types of carbonate fillers. The limestone powder has fine particles, which can optimize the fluidity of materials such as cement and act as a filler to reduce pores. Shell powder has a plasticizing effect to a certain extent because it contains organic components, and cooperates with limestone powder to make the slurry easier to stir and pump. The active magnesium oxide component in the magnesite tailings reacts slowly with water in the later stage to form magnesium hydroxide gel, which fills the internal pores and makes the material structure denser. The three together improve the compressive and flexural strength. In addition, the calcium carbonate component in the limestone powder and shell powder can react with the cement hydration product in an alkaline environment to enhance the material's impermeability. The magnesia minerals in the magnesite tailings, the gel formed by the reaction, also block the pores and prevent the invasion of external moisture and chloride ions.
[0029] In a preferred embodiment, the preparation method of the fine aggregate is as follows:
[0030] The quartz sand is acidified and then washed, and then dried and mixed with magnesium nitrate, aluminum nitrate and water, and the pH is adjusted to 10-12. After the reaction, it is filtered and washed to obtain fine aggregate.
[0031] In a preferred embodiment, the quartz sand is a mixture of quartz sand with an average particle size of 50-100 nm, quartz sand with an average particle size of 100-200 nm, and quartz sand with an average particle size of 1-5 μm;
[0032] The mass ratio of the quartz sand with an average particle size of 50-100 nm, the quartz sand with an average particle size of 100-200 nm and the quartz sand with an average particle size of 1-5 μm is 100:(40-60):(5-10).
[0033] In a preferred embodiment, the specific conditions for the acidification are: soaking in 0.1 mol / L nitric acid solution for 20-28 hours.
[0034] In a preferred embodiment, the mass ratio of quartz sand, magnesium nitrate, aluminum nitrate and water is 100: (100-200): (50-150): (500-1000).
[0035] In a preferred embodiment, the reaction conditions are: stirring the reaction at 40-60°C for 1-3h, and then stirring the reaction at 60-100°C for 6-10h.
[0036] The present invention greatly enhances the anti-chloride ion penetration performance by modifying the fine aggregate. It should be noted that the present invention has good anti-chloride ion permeability through carbonate fillers, but calcium carbonate will release carbon dioxide and form soluble salts when it encounters acid, which affects the acid resistance of the filler. Its structure and performance are easily destroyed in an acidic environment. At this time, the present invention greatly reduces the defects of carbonate fillers through the curing effect of the added fine aggregate. This is mainly because the magnesium-aluminum layered double hydroxide and quartz sand form a core-shell structure, and the quartz sand of various particle sizes compounded by the present invention effectively fills the carbonate filler around, making its distribution more uniform. Specifically, the magnesium-aluminum layered double hydroxide changes the surface state of the quartz sand, making its surface rougher and having a larger specific surface area. And because the magnesium-aluminum layered double hydroxide coating has a strong adsorption capacity for chloride ions, the pores and defects formed in the interface transition zone in the formed cement are less, the critical pore size is reduced, and the pore structure of the mortar is refined. The reduction of this large capillary ratio can delay the transmission of chloride ions, eliminating the adverse effects on carbonate fillers from the aspects of curing and blocking.
[0037] In a preferred embodiment, the cement clinker comprises the following components in parts by weight: 55-65 parts of tricalcium silicate; 10-15 parts of dicalcium silicate; 10-15 parts of calcium aluminate; 5-10 parts of tetracalcium aluminoferrite; and 0.5-1 part of loss on ignition.
[0038] In a preferred embodiment, the aluminum-rich mineral correcting material includes one or more of metakaolin, fly ash, and bauxite tailings;
[0039] The condition is that the content of alumina in the aluminum-rich mineral corrective material is greater than 30 parts relative to 100 parts by weight of the aluminum-rich mineral corrective material.
[0040] In a preferred embodiment, the sulfate component includes one or more of dihydrate gypsum, desulfurized gypsum, and phosphogypsum;
[0041] The condition is that the calcium sulfate content in the sulfate component is greater than 90 parts relative to 100 parts by weight of the sulfate component.
[0042] In a preferred embodiment, the performance improver includes one or more of diethanolamine salt, triethanolamine salt, and alkylbenzene sulfonic acid.
[0043] The second aspect of the present invention provides a method for preparing the above-mentioned coal gangue-based low-carbon cement with high resistance to chloride ion penetration, comprising the following steps:
[0044] (1) drying the gangue raw material, adding water and controlling the water content to 8-10 parts, placing it in an autoclave for autoclave hydrothermal treatment at a pressure of 1.2-1.5 MPa and a temperature of 100-150° C., then wet grinding the solid phase after the reaction for 20-40 min at a ball-to-material ratio of 2:1-3:1, drying and microwave activation to obtain;
[0045] (2) First, cement clinker, coal gangue and sulfate components are mixed and ball-milled once, then aluminum-rich mineral corrective materials are added and ball-milled twice, then carbonate fillers and fine aggregates are added and ball-milled three times, and finally, performance improvers are added and ball-milled four times to obtain coal gangue-based low-carbon cement.
[0046] In a preferred embodiment, in step (1), the specific conditions of the microwave activation are: microwave power 400-600W, temperature 600-700°C, time 2-3h.
[0047] Compared with the prior art, the advantages and beneficial effects of the present invention are:
[0048] 1. The present invention modifies limestone powder, shell powder and magnesite tailings by styrene acrylic emulsion, so that the cement clinker has excellent toughness, strength and high chloride ion resistance, thereby overcoming the disadvantages of relatively high porosity and poor impermeability of coal gangue cement.
[0049] 2. The present invention significantly improves the strength and chloride ion permeability of cement by compounding the types of carbonate fillers. The limestone powder has fine particles, which can optimize the fluidity of cement and other materials, and act as a filler to reduce pores. Shell powder has a plasticizing effect to a certain extent because it contains organic components, and cooperates with limestone powder to make the slurry easier to stir and pump. The active magnesium oxide component in the magnesite tailings reacts slowly with water in the later stage to form magnesium hydroxide gel, which fills the internal pores and makes the material structure denser. The three together improve the compressive and flexural strength. In addition, the calcium carbonate component in the limestone powder and shell powder can react with the cement hydration product in an alkaline environment to enhance the material's impermeability. The magnesia minerals in the magnesite tailings also block the pores and prevent the invasion of external moisture and chloride ions through the gel formed by the reaction.
[0050] 3. The present invention greatly enhances the chloride ion penetration resistance by modifying the fine aggregate. It should be noted that the present invention has good chloride ion penetration resistance through carbonate fillers, but calcium carbonate will release carbon dioxide and form soluble salts when encountering acid, which affects the acid resistance of the filler. Its structure and performance are easily destroyed in an acidic environment. At this time, the present invention greatly reduces the defects of carbonate fillers through the solidification effect of the added fine aggregate.
[0051] 4. In the present invention, the aluminate phase and the carbonate phase react in the cement hydration system to generate more CO3-AFm, and the balance of carbonate and sulfate in the system is adjusted by introducing sulfate components and performance improvers to achieve the purpose of stabilizing the presence of ettringite and ensuring volume stability. The large volume of hydration product ettringite will cut off the transmission channel of chloride ions and realize the physical solidification of chloride ions. The CSH gel product will chemically adsorb chloride ions, and CO3-AFm will solidify chloride ions to form a hydration product Friedel salt precipitation, further preventing chloride ions from diffusing in the system. BRIEF DESCRIPTION OF THE DRAWINGS
[0052] Figure 1 This is a schematic diagram of a scanning electron microscope (SEM) of the cement obtained in Examples 1 to 4. DETAILED DESCRIPTION
[0053] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0054] In the following examples and comparative examples, unless otherwise specified, all raw materials used were commercially available or prepared by conventional methods in the art.
[0055] Cement clinker, PO 42.5, was purchased from Conch Cement;
[0056] Metakaolin, product number 427, was purchased from Wuhan Jiyesheng Chemical Co., Ltd.;
[0057] Fly ash, product number A01085, was purchased from Wuhan Jiyesheng Chemical Co., Ltd.;
[0058] Bauxite tailings, item number H2134, purchased from Yangquan Guangtai Magnesium Co., Ltd.;
[0059] Limestone, with an average particle size of 100 nm, was purchased from Chizhou Langhe Fine Calcium Industry Co., Ltd.;
[0060] Shell powder, with an average particle size of 200 nm, was purchased from Xuanguang Mineral Products Processing Plant in Lingshou County;
[0061] Magnesite tailings, with an average particle size of 0.3 mm, were purchased from Haicheng Hailing Mining Co., Ltd.;
[0062] Quartz sand, average particle size of 80 nm, 150 nm, and 3 μm: purchased from Qingdao Kaiwell Powder Engineering Technology Co., Ltd.
[0063] Example 1
[0064] This embodiment provides a gangue-based low-carbon cement with high resistance to chloride ion penetration, comprising the following steps:
[0065] 1. Raw material processing:
[0066] By mass, 40 parts of cement clinker, 30 parts of coal gangue, 10 parts of aluminum-rich mineral corrective material, 15 parts of carbonate filler, 12 parts of fine aggregate, and 5 parts of sulfate components are dried, and all the materials are sieved through a 200-mesh sieve.
[0067] The cement clinker includes the following components by weight: 60 parts of tricalcium silicate; 12 parts of dicalcium silicate; 13 parts of calcium aluminate; 8 parts of tetracalcium aluminoferrite; and 0.6 parts of loss on ignition.
[0068] The aluminum-rich mineral correcting material includes the following components in parts by weight: 1 part of metakaolin, 2 parts of fly ash, and 3 parts of bauxite tailings, and the content of aluminum oxide in the aluminum-rich mineral correcting material is 45 parts relative to 100 parts by weight of the aluminum-rich mineral correcting material.
[0069] The preparation method of carbonate filler is as follows:
[0070] By mass, 1 part of limestone, 4 parts of shell powder and 8 parts of magnesite tailings were ground and passed through a 200-mesh sieve to obtain a solid phase. 1 part of the solid phase was mixed with 6 parts of styrene, 14 parts of acrylate, 50 parts of anhydrous ethanol and 80 parts of water. 6 parts of potassium persulfate were added, and the mixture was refluxed at 60°C for 6 hours. The carbonate filler was obtained by filtering and washing.
[0071] The preparation method of fine aggregate is as follows:
[0072] By mass, 100 parts of quartz sand were soaked in 0.1 mol / L nitric acid solution for 24 hours and then washed, wherein the mass ratio of quartz sand with an average particle size of 80 nm, quartz sand with an average particle size of 150 nm and quartz sand with an average particle size of 3 μm was 10:5:1. After drying, they were mixed with 150 parts of magnesium nitrate, 50 parts of aluminum nitrate and 700 parts of water, the pH was adjusted to 11, and the reaction was stirred at 50°C for 2 hours, then stirred at 80°C for 8 hours, and filtered and washed to obtain fine aggregate.
[0073] The sulfate component includes the following components in parts by weight: 1 part of dihydrate gypsum, 2 parts of desulfurized gypsum, and 3 parts of phosphogypsum, and the content of calcium sulfate in the sulfate component is 92 parts relative to 100 parts by weight of the sulfate component.
[0074] 2. Mixed step grinding preparation:
[0075] First, cement clinker, pretreated coal gangue and sulfate components are uniformly mixed according to the said proportions and then placed in a ball mill to control the ball-to-material ratio to 3:1 and grind for 15 minutes; second, aluminum-rich mineral corrective material is added and grinding is continued for 15 minutes; third, carbonate filler and fine aggregate are added and grinding is continued for 150 minutes; fourth, 0.2 parts of performance improver are added and grinding is continued for 8 minutes, and the specific surface area of the final coal gangue-based low-carbon cement with high resistance to chloride ion penetration is controlled to be 800-1000m 2 / kg, D 50 10-15μm.
[0076] The grinding equipment uses a vertical planetary ball mill for grinding. The grinding jar is made of stainless steel, coated with polyurethane inside, and has a volume of 1L. In the continuous grading, stainless steel balls with a particle size distribution of 2, 4, 6, 8, and 10 mm are used as grinding media. Each grinding jar is loaded with 1.5 kg of steel balls. The ball-to-material weight ratio is 2:1, and the grinding speed is 300 rpm.
[0077] Example 2
[0078] This embodiment provides a gangue-based low-carbon cement with high resistance to chloride ion penetration, comprising the following steps:
[0079] 1. Raw material processing:
[0080] By mass, 30 parts of cement clinker, 40 parts of coal gangue, 10 parts of aluminum-rich mineral corrective material, 15 parts of carbonate filler, 12 parts of fine aggregate, and 5 parts of sulfate components are dried, and all the materials are sieved through a 200-mesh sieve.
[0081] The cement clinker includes the following components by weight: 60 parts of tricalcium silicate; 12 parts of dicalcium silicate; 13 parts of calcium aluminate; 8 parts of tetracalcium aluminoferrite; and 0.6 parts of loss on ignition.
[0082] The aluminum-rich mineral correcting material includes the following components in parts by weight: 1 part of metakaolin, 2 parts of fly ash, and 3 parts of bauxite tailings, and the content of aluminum oxide in the aluminum-rich mineral correcting material is 45 parts relative to 100 parts by weight of the aluminum-rich mineral correcting material.
[0083] The preparation method of carbonate filler is as follows:
[0084] By mass, 1 part of limestone, 4 parts of shell powder and 8 parts of magnesite tailings were ground and passed through a 200-mesh sieve to obtain a solid phase. 1 part of the solid phase was mixed with 6 parts of styrene, 14 parts of acrylate, 50 parts of anhydrous ethanol and 80 parts of water. 6 parts of potassium persulfate were added, and the mixture was refluxed at 60°C for 6 hours. The carbonate filler was obtained by filtering and washing.
[0085] The preparation method of fine aggregate is as follows:
[0086] By mass, 100 parts of quartz sand were soaked in 0.1 mol / L nitric acid solution for 24 hours and then washed, wherein the mass ratio of quartz sand with an average particle size of 80 nm, quartz sand with an average particle size of 150 nm and quartz sand with an average particle size of 3 μm was 10:5:1. After drying, they were mixed with 150 parts of magnesium nitrate, 50 parts of aluminum nitrate and 700 parts of water, the pH was adjusted to 11, and the reaction was stirred at 50°C for 2 hours, then stirred at 80°C for 8 hours, and filtered and washed to obtain fine aggregate.
[0087] The sulfate component includes the following components in parts by weight: 1 part of dihydrate gypsum, 2 parts of desulfurized gypsum, and 3 parts of phosphogypsum, and the content of calcium sulfate in the sulfate component is 92 parts relative to 100 parts by weight of the sulfate component.
[0088] 2. Mixed step grinding preparation:
[0089] First, cement clinker, pretreated coal gangue and sulfate components are uniformly mixed according to the said proportions and then placed in a ball mill to control the ball-to-material ratio to 3:1 and grind for 15 minutes; second, aluminum-rich mineral corrective material is added and grinding is continued for 15 minutes; third, carbonate filler and fine aggregate are added and grinding is continued for 150 minutes; fourth, 0.2 parts of performance improver are added and grinding is continued for 8 minutes, and the specific surface area of the final coal gangue-based low-carbon cement with high resistance to chloride ion penetration is controlled to be 800-1000m 2 / kg, D 50 10-15μm.
[0090] The grinding equipment uses a vertical planetary ball mill for grinding. The grinding jar is made of stainless steel, coated with polyurethane inside, and has a volume of 1L. In the continuous grading, stainless steel balls with a particle size distribution of 2, 4, 6, 8, and 10 mm are used as grinding media. Each grinding jar is loaded with 1.5 kg of steel balls. The ball-to-material weight ratio is 2:1, and the grinding speed is 300 rpm.
[0091] Example 3
[0092] This embodiment provides a gangue-based low-carbon cement with high resistance to chloride ion penetration, comprising the following steps:
[0093] 1. Raw material processing:
[0094] By mass, 40 parts of cement clinker, 30 parts of coal gangue, 15 parts of aluminum-rich mineral corrective material, 10 parts of carbonate filler, 12 parts of fine aggregate, and 5 parts of sulfate components are dried, and all the materials are sieved through a 200-mesh sieve.
[0095] The cement clinker includes the following components by weight: 60 parts of tricalcium silicate; 12 parts of dicalcium silicate; 13 parts of calcium aluminate; 8 parts of tetracalcium aluminoferrite; and 0.6 parts of loss on ignition.
[0096] The aluminum-rich mineral correcting material includes the following components in parts by weight: 1 part of metakaolin, 2 parts of fly ash, and 3 parts of bauxite tailings, and the content of aluminum oxide in the aluminum-rich mineral correcting material is 45 parts relative to 100 parts by weight of the aluminum-rich mineral correcting material.
[0097] The preparation method of carbonate filler is as follows:
[0098] By mass, 1 part of limestone, 4 parts of shell powder and 8 parts of magnesite tailings were ground and passed through a 200-mesh sieve to obtain a solid phase. 1 part of the solid phase was mixed with 6 parts of styrene, 14 parts of acrylate, 50 parts of anhydrous ethanol and 80 parts of water. 6 parts of potassium persulfate were added, and the mixture was refluxed at 60°C for 6 hours. The carbonate filler was obtained by filtering and washing.
[0099] The preparation method of fine aggregate is as follows:
[0100] By mass, 100 parts of quartz sand were soaked in 0.1 mol / L nitric acid solution for 24 hours and then washed. The mass ratio of quartz sand with an average particle size of 80 nm, quartz sand with an average particle size of 150 nm and quartz sand with an average particle size of 3 μm was 10:5:1. After drying, they were mixed with 150 parts of magnesium nitrate, 50 parts of aluminum nitrate and 700 parts of water. The pH was adjusted to 11. The mixture was stirred and reacted at 50°C for 2 hours and then at 80°C for 8 hours. The fine aggregate was filtered and washed.
[0101] The sulfate component includes the following components in parts by weight: 1 part of dihydrate gypsum, 2 parts of desulfurized gypsum, and 3 parts of phosphogypsum, and the content of calcium sulfate in the sulfate component is 92 parts relative to 100 parts by weight of the sulfate component.
[0102] 2. Mixed step grinding preparation:
[0103] First, cement clinker, pretreated coal gangue and sulfate components are uniformly mixed according to the said proportions and then placed in a ball mill to control the ball-to-material ratio to 3:1 and grind for 15 minutes; second, aluminum-rich mineral corrective material is added and grinding is continued for 15 minutes; third, carbonate filler and fine aggregate are added and grinding is continued for 150 minutes; fourth, 0.2 parts of performance improver are added and grinding is continued for 8 minutes, and the specific surface area of the final coal gangue-based low-carbon cement with high resistance to chloride ion penetration is controlled to be 800-1000m 2 / kg, D 50 10-15μm.
[0104] The grinding equipment uses a vertical planetary ball mill for grinding. The grinding jar is made of stainless steel, coated with polyurethane inside, and has a volume of 1L. In the continuous grading, stainless steel balls with a particle size distribution of 2, 4, 6, 8, and 10 mm are used as grinding media. Each grinding jar is loaded with 1.5 kg of steel balls. The ball-to-material weight ratio is 2:1, and the grinding speed is 300 rpm.
[0105] Example 4
[0106] This embodiment provides a gangue-based low-carbon cement with high resistance to chloride ion penetration, comprising the following steps:
[0107] 1. Raw material processing:
[0108] By mass, 40 parts of cement clinker, 30 parts of coal gangue, 5 parts of aluminum-rich mineral corrective materials, 20 parts of carbonate fillers, 12 parts of fine aggregates, and 5 parts of sulfate components are dried, and all the materials are sieved through a 200-mesh sieve.
[0109] The cement clinker includes the following components by weight: 60 parts of tricalcium silicate; 12 parts of dicalcium silicate; 13 parts of calcium aluminate; 8 parts of tetracalcium aluminoferrite; and 0.6 parts of loss on ignition.
[0110] The aluminum-rich mineral correcting material includes the following components in parts by weight: 1 part of metakaolin, 2 parts of fly ash, and 3 parts of bauxite tailings, and the content of aluminum oxide in the aluminum-rich mineral correcting material is 45 parts relative to 100 parts by weight of the aluminum-rich mineral correcting material.
[0111] The preparation method of carbonate filler is as follows:
[0112] By mass, 1 part of limestone, 4 parts of shell powder and 8 parts of magnesite tailings were ground and passed through a 200-mesh sieve to obtain a solid phase. 1 part of the solid phase was mixed with 6 parts of styrene, 14 parts of acrylate, 50 parts of anhydrous ethanol and 80 parts of water. 6 parts of potassium persulfate were added, and the mixture was refluxed at 60°C for 6 hours. The carbonate filler was obtained by filtering and washing.
[0113] The preparation method of fine aggregate is as follows:
[0114] By mass, 100 parts of quartz sand were soaked in 0.1 mol / L nitric acid solution for 24 hours and then washed. The mass ratio of quartz sand with an average particle size of 80 nm, quartz sand with an average particle size of 150 nm and quartz sand with an average particle size of 3 μm was 10:5:1. After drying, they were mixed with 150 parts of magnesium nitrate, 50 parts of aluminum nitrate and 700 parts of water. The pH was adjusted to 11. The mixture was stirred and reacted at 50°C for 2 hours and then at 80°C for 8 hours. The fine aggregate was filtered and washed.
[0115] The sulfate component includes the following components in parts by weight: 1 part of dihydrate gypsum, 2 parts of desulfurized gypsum, and 3 parts of phosphogypsum, and the content of calcium sulfate in the sulfate component is 92 parts relative to 100 parts by weight of the sulfate component.
[0116] 2. Mixed step grinding preparation:
[0117] First, cement clinker, pretreated coal gangue and sulfate components are uniformly mixed according to the said proportions and then placed in a ball mill to control the ball-to-material ratio to 3:1 and grind for 15 minutes; second, aluminum-rich mineral corrective material is added and grinding is continued for 15 minutes; third, carbonate filler and fine aggregate are added and grinding is continued for 150 minutes; fourth, 0.2 parts of performance improver are added and grinding is continued for 8 minutes, and the specific surface area of the final coal gangue-based low-carbon cement with high resistance to chloride ion penetration is controlled to be 800-1000m 2 / kg, D 50 10-15μm.
[0118] The grinding equipment uses a vertical planetary ball mill for grinding. The grinding jar is made of stainless steel, coated with polyurethane inside, and has a volume of 1L. In the continuous grading, stainless steel balls with a particle size distribution of 2, 4, 6, 8, and 10 mm are used as grinding media. Each grinding jar is loaded with 1.5 kg of steel balls. The ball-to-material weight ratio is 2:1, and the grinding speed is 300 rpm.
[0119] Comparative Example 1
[0120] The difference between this comparative example and Example 1 is that no fine aggregate is added, and the aluminum-rich mineral corrective material is changed to 16 parts, and the carbonate filler is changed to 21 parts.
[0121] Comparative Example 2
[0122] The difference between this comparative example and Example 1 is that no carbonate filler is added, and the aluminum mineral correcting material is changed to 17.5 parts and the fine aggregate is changed to 19.5 parts.
[0123] Comparative Example 3
[0124] The difference between this comparative example and Example 1 is that no aluminum-rich mineral corrective material is added, and the carbonate filler is changed to 20 parts and the fine aggregate is changed to 17 parts.
[0125] Comparative Example 4
[0126] The difference between this comparative example and Example 1 is that the carbonate filler only includes limestone, shell powder and magnesite tailings.
[0127] Comparative Example 5
[0128] The difference between this comparative example and Example 1 is that the preparation method of the carbonate filler is as follows:
[0129] By mass, 4.5 parts of shell powder and 8.5 parts of dolomite tailings were ground and passed through a 200-mesh sieve to obtain a solid phase. 1 part of the solid phase was mixed with 6 parts of styrene, 14 parts of acrylate, 50 parts of anhydrous ethanol, and 80 parts of water. 6 parts of potassium persulfate were added, and the mixture was refluxed at 60°C for 6 hours. The carbonate filler was obtained by filtering and washing.
[0130] Comparative Example 6
[0131] The difference between this comparative example and Example 1 is that the fine aggregate only includes quartz sand.
[0132] Performance Testing
[0133] The mortar samples of low-carbon cement based on coal gangue with high resistance to chloride ion penetration were prepared with reference to GB / T 175-2008 "Test Method for Cement Mortar Strength" and the flexural strength and compressive strength were tested. The chloride ion flux and permeability coefficient of the mortar samples of low-carbon cement based on coal gangue with high resistance to chloride ion penetration were tested according to GB / T 50082-2009 "Standard for Test Methods for Long-term Performance and Durability of Ordinary Concrete", and the results are shown in Table 1.
[0134] Table 1 Performance test results
[0135]
[0136] It can be seen from the above performance test results that Examples 1-4 have excellent high resistance to chloride ion permeability. In addition, the toughness and strength of the cement are also greatly improved. In particular, the comprehensive performance of Example 1 is the most outstanding. This is mainly because the present invention, through the synergistic effect of carbonate filler and fine aggregate, and the synergistic effect of aluminum-rich mineral corrective material and carbonate filler, makes the cement clinker have excellent toughness, strength, and high chloride ion resistance, thereby overcoming the shortcomings of coal gangue cement with relatively high porosity and poor impermeability.
[0137] To further verify the principle of the present invention, the present invention used SEM to observe the microstructure of samples of different embodiments. The results are as follows: Figure 1 shown. Figure 1 It can be seen that the gangue-based low-carbon cement matrix with high resistance to chloride ion penetration has a dense structure and low porosity. The matrix is tightly filled with gel hydration products and there are many large-volume hydration products AFm that can further solidify chloride ions.
[0138] The comparative example does not adopt the necessary technical solution, resulting in its performance being significantly worse than that of the embodiment in the corresponding performance test. This better proves the irreplaceable nature of the specific technical solution of the present application in achieving technical effects and solving technical problems.
[0139] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A coal gangue-based low-carbon cement with high resistance to chloride ion penetration, characterized in that: It includes the following components by weight: 30-50 parts of cement clinker; 30-50 parts of coal gangue; 5-15 parts of aluminum-rich mineral correction material; 10-20 parts of carbonate filler; 10-15 parts of fine aggregate; Sulfate component 5-10 parts; Performance improver 0.4-0.8 parts; The carbonate filler is obtained by modifying limestone powder, shell powder and magnesite tailings with styrene acrylate emulsion; The preparation method of the carbonate filler is as follows: Limestone, shell powder and magnesite tailings are ground and sieved to obtain a solid phase, the solid phase is mixed with styrene, acrylate, anhydrous ethanol and water, an initiator is added, and after reaction, the carbonate filler is obtained by filtering and washing.
2. The gangue-based low-carbon cement with high resistance to chloride ion penetration according to claim 1, characterized in that: The mass ratio of the limestone, shell powder and magnesite tailings is 1:(2-5):(4-10); And / or, the sieve used for the sieving is 200-500 mesh; and / or, the mass ratio of the solid phase, styrene, acrylate, initiator, anhydrous ethanol and water is 1:(5-8):(10-17):(2-8):(42-63):(60-100); And / or, the initiator is potassium persulfate; And / or, the reaction is a reflux reaction, the reaction temperature is 50-80° C., and the reaction time is 3-8 h.
3. The gangue-based low-carbon cement with high resistance to chloride ion penetration according to claim 1, characterized in that: The preparation method of the fine aggregate is as follows: The quartz sand is acidified and then washed, and then dried and mixed with magnesium nitrate, aluminum nitrate and water, and the pH is adjusted to 10-12. After the reaction, it is filtered and washed to obtain fine aggregate.
4. The gangue-based low-carbon cement with high resistance to chloride ion penetration according to claim 3, characterized in that: The quartz sand is a mixture of quartz sand with an average particle size of 50-100 nm, quartz sand with an average particle size of 100-200 nm, and quartz sand with an average particle size of 1-5 μm; The mass ratio of the quartz sand with an average particle size of 50-100 nm, the quartz sand with an average particle size of 100-200 nm and the quartz sand with an average particle size of 1-5 μm is 100: (40-60): (5-10); And / or, the specific conditions of the acidification are: soaking in 0.1 mol / L nitric acid solution for 20-28 hours; And / or, the mass ratio of quartz sand, magnesium nitrate, aluminum nitrate and water is 100: (100-200): (50-150): (500-1000); And / or, the reaction conditions are: stirring the reaction at 40-60° C. for 1-3 h, and then stirring the reaction at 60-100° C. for 6-10 h.
5. The gangue-based low-carbon cement with high resistance to chloride ion penetration according to claim 1, characterized in that: The cement clinker comprises the following components by weight: 55-65 parts of tricalcium silicate; 10-15 parts of dicalcium silicate; 10-15 parts of calcium aluminate; 5-10 parts of tetracalcium aluminoferrite; Loss on ignition 0.5-1 part.
6. The gangue-based low-carbon cement with high resistance to chloride ion penetration according to claim 1, characterized in that: The aluminum-rich mineral correction material includes one or more of metakaolin, fly ash, and bauxite tailings; The condition is that the content of alumina in the aluminum-rich mineral corrective material is greater than 30 parts relative to 100 parts by weight of the aluminum-rich mineral corrective material.
7. The gangue-based low-carbon cement with high resistance to chloride ion penetration according to claim 1, characterized in that: The sulfate component includes one or more of dihydrate gypsum, desulfurized gypsum, and phosphogypsum; The condition is that the calcium sulfate content in the sulfate component is greater than 90 parts relative to 100 parts by weight of the sulfate component.
8. The gangue-based low-carbon cement with high resistance to chloride ion penetration according to claim 1, characterized in that: The performance improver includes one or more of diethanolamine salt, triethanolamine salt and alkylbenzene sulfonic acid.
9. A method for preparing the gangue-based low-carbon cement with high resistance to chloride ion penetration as claimed in any one of claims 1 to 8, characterized in that: The following steps are involved: (1) drying the gangue raw material, adding water and controlling the water content to 8-10 parts, placing it in an autoclave for autoclave hydrothermal treatment at a pressure of 1.2-1.5 MPa and a temperature of 100-150° C., then wet grinding the solid phase after the reaction for 20-40 min at a ball-to-material ratio of 2:1-3:1, drying and microwave activation to obtain; (2) First, cement clinker, coal gangue and sulfate components are mixed and ball milled once, then aluminum-rich mineral corrective materials are added and ball milled twice, carbonate fillers and fine aggregates are added again and ball milled three times, and finally a performance improver is added and ball milled four times to obtain coal gangue-based low-carbon cement; In step (1), the specific conditions of the microwave activation are: microwave power 400-600W, temperature 600-700°C, and time 2-3h.
Citation Information
Patent Citations
Low-carbon cement clinker and preparation method and application thereof
CN105669056A
Method for preparing cement clinker by using coal gangue as raw material
CN119118541A
Arsenic-containing waste slag solidified body and preparation method thereof
CN102249609A
Retarded cement prepared from fluidized bed combustion ash and coal gangue and preparation method of cement
CN113831035A